Pengaruh Media Paper Plate Terhadap Kemampuan Keaksaraan Anak Usia 5-6 Tahun di TK Negeri Pembina Karawang - Wahyu Laily Putri Rachmawati; Rina Syafrida; Ine Nirmala (Jurnal Ilmiah Wahana Pendidikan, 2022)
This research was conducted based on the results of observations made by researchers and then found the problems that existed in Pembina Karawang State Kindergarten, namely the literacy skills of children aged 5-6 years were still low, such as the low ability of children to recognize letter symbols, mention the letters of clouds from an object, classifying sounds and letters, and write letter symbols. Based on these problems, researchers provide solutions to develop paper plate media to improve early childhood literacy skills. This study aims to determine whether paper plate media has an effect on increasing literacy skills of children aged 5-6 years in Pembina Karawang State Kindergarten. This research is an experimental quantitative research. The subjects in this study were students of group B2. The results of this study prove that paper plate media has an effect on the literacy skills of children aged 5-6 years in Pembina Karawang State Kindergarten. This can be seen in the results of the t test or hypothesis testing. Hypothesis testing in this study shows that the results tcount > ttable (12,244 > 1,734) which means Ho is rejected and Ha is accepted. From these results, there is a difference between the average pretest and posttest, therefore there is a significant influence on the use of paper plate media with the literacy skills of children aged 5-6 years